Fit for war : sustenance and order in the mid-eighteenth-century Catawba Nation - Fitts, Mary Elizabeth (Florida Museum of Natural History. Ripley P. Bullen series, 2018)
In the mid-18th century, the towns of the Catawba Nation were located near Nation Ford, where the main trading path that traversed the southern Appalachian Piedmont crossed the Catawba River. By serving as auxiliaries for the English colonies, particularly South Carolina, Catawba men from these communities had achieved notoriety and helped maintain the political autonomy of the Nation. However, this militaristic strategy precipitated a set of processes that transformed the conditions of daily life near Nation Ford. Two of these processes were settlement aggregation and the incorporation of native refugee communities. This work examines whether the political process of centralization through which refugees were incorporated into the Catawba Nation was accompanied by parallel changes in economic organization, particularly with regard to foodways.